Very Rare Case of Hyaline Fibromatosis Syndrome Successfully Treated with Surgical Excision and Review of Literature - Jung, Yong Uk; Kim, Byung-jun; Kim, Eun-Hee (Archives of Plastic Surgery, 2025)
Hyaline fibromatosis syndrome (HFS) is a rare autosomal recessive disorder caused by ANTXR2 gene mutations, resulting in abnormal deposition of hyaline material in connective tissues. Fewer than 100 cases have been documented worldwide. Patients often present with painful joint contractures, gingival hyperplasia, cutaneous nodules, and restricted mobility. Here, we report a 7-year-old boy with HFS who underwent surgical management for near-total obstruction of the external ear canal and multiple ulcerative lesions. A multidisciplinary approach facilitated successful mass excision and reconstruction with a split-thickness skin graft. Postoperative evaluations showed stable wound healing at 6 months, allowing consideration of further surgeries. This case highlights the importance of comprehensive genetic assessment, careful preoperative planning, and individualized surgical intervention, as well as the critical role of nutritional support to optimize wound healing and clinical outcomes in HFS.
Keywords: hyaline fibromatosis syndrome; skin graft; reconstruction; review of literature